Global Income Distribution : From the Fall of the Berlin Wall to the Great Recession - Lakner, Christoph; Milanovic, Branko (World Bank, Washington, DC, 2014)
The paper presents a newly compiled and improved database of national household surveys between 1988 and 2008. In 2008, the global Gini index is around 70.5 percent having declined by approximately 2 Gini points over this twenty year period. When it is adjusted for the likely under-reporting of top incomes in surveys by using the gap between national accounts consumption and survey means in combination with a Pareto-type imputation of the upper tail, the estimate is a much higher global Gini of almost 76 percent. With such an adjustment the downward trend in the Gini almost disappears. Tracking the evolution of individual country-deciles shows the underlying elements that drive the changes in the global distribution: China has graduated from the bottom ranks, modifying the overall shape of the global income distribution in the process and creating an important global "median" class that has transformed a twin-peaked 1988 global distribution into an almost single-peaked one now. The "winners" were country-deciles that in 1988 were around the median of the global income distribution, 90 percent of whom in terms of population are from Asia. The "losers" were the country-deciles that in 1988 were around the 85th percentile of the global income distribution, almost 90 percent of whom in terms of population are from mature economies.